Conception Magico- Religieuse Des Agressions Sexuelles Et Du Viol Des Filles De 04 Mois A 18 Ans A L’ouest De La Côte D’ivoire (Duékoué Et Guiglo) - Koko Lucie N’goran; Ismaila Bakayoko; Agbadou Nakpon Joceline-Boli (European Scientific Journal, ESJ, 2016)
This article aims to study the sexual aggression and rape of minors in the western region of Côte d'Ivoire. The results show that as any deviancy, rape is a phenomenon which is explained by the imaginary conception of individuals and sociocultural representations design (see the designs put). Thus, acceptance and trivialization of violent sexual act or not, the submission idea of male domination and the negative attitude towards women are the key variables in explaining the rape. The choice of amicable settlements contributes to the aggravation of the phenomenon.